Keterwakilan Perempuan dalam Politik Indonesia: Tren, Capaian, dan Jalan Panjang Menuju Kesetaraan - Indra Kertati (Universitas 17 Agustus 1945 Semarang, 2025)
This study aims to analyze the structural, cultural, and institutional barriers affecting women's political representation in Indonesia and to formulate strategic recommendations to strengthen the effectiveness of affirmative action policies. Although a 30% quota policy for women's representation on legislative candidate lists has been implemented, this achievement generally only serves as an administrative requirement and does not guarantee substantive opportunities in the political process. The study uses a qualitative descriptive approach based on secondary data obtained from official government documents, international organization reports, statistical publications, and previous research. The analysis shows that structural barriers manifest themselves in the placement of the majority of female legislative candidates on less strategic ticket numbers, resulting in low electability, and significant disparities in access to campaign funding between male and female candidates. Cultural barriers include entrenched gender stereotypes, reflected in surveys showing that only around 35% of the public supports female political leadership. Institutional barriers are also evident in the low representation of women in the executive and judicial branches, with only one female governor and one female constitutional judge currently serving. Based on these findings, the study recommends several strategic steps, including strengthening substantive affirmative action policies through regulating legislative candidate ticket numbers, providing equal affirmative action campaign funding, implementing career acceleration schemes for women in public office, implementing programs to strengthen women's political capacity, and promoting gender literacy campaigns to change public perceptions. This study emphasizes that the success of affirmative action policies cannot simply rely on quota regulations, but requires multi-level interventions that include legislative reform, improvements to political recruitment mechanisms, and transformation of social values. These integrated efforts are expected to encourage a sustainable increase in women's political representation and achieve gender equality in the Indonesian political system.